(untitled)
bl ’kks/k i= esa o"kZ 1961 ls 2008 ds nkSjku Hkkjr esa lrg ds fudV iou xfr esa gq, ifjorZuksa dk fo’ys"k.k fd;k x;k gSA 171 LVs’kuksa ds ekfld iou xfr vkadM+ksa ds fo’ys"k.k ls izkIr ifj.kke crkrs gSa fd Hkkjr ds vf/kdrj LVs’kuksa ij iou xfr esa ekfld vkSj okf"kZd nksuksa gh fLFkfr;kssa esa egRoiw.kZ :i ls deh ns[kh xbZ gSA lewps Hkkjr esa okf"kZd iou xfr ek/; dk vkSlr o"kZ 1961 ds 9-7 fd-eh- izfr ?kaVk ls ?kVdj o"kZ 2008 esa 5-0 fd-eh- izfr ?kaVk gks x;k gS tks 49 izfr’kr dh deh dks n’kkZrk gSA lewps Hkkjr esa iou xfr ds okf"kZd vkSlr esa fxjkoV dh vkSlr nj &0-88 fd-eh- izfr ?kaVk izfr n’kd ikbZ xbZ gSA ekfld iSekus ij lcls vf/kd fxjkoV dh nj twu esa ¼&1-33 fd-eh- izfr ?kaVk izfr n’kd½ vkSj lcls de vDrwcj esa ¼&0-60 fd-eh- izfr?kaVk izfr n’kd½ ikbZ xbZ gSA LFkkfud rkSj ij lcls vf/kd fxjkoV if’peh Hkkjr] nfk.kh izk;hi rFkk leqnz rVh; ks=ksa esa ikbZ xbZ gS tcfd e/; nfk.k iwoZ ,oa iwokZsRrj Hkkjr esa iou xfr esa de ifjorZu ns[kk x;k gSA iou xfr esa egRoiw.kZ :i ls fxjkoV eq[;r% xqtjkr] egkjk"Vª] rfeyukMq] mRrjh dukZVd] rVh; mM+hlk ,oa rVh; if’pe caxky ds ks=ksa esa ikbZ xbZ gS ftuesa iou xfr dk okf"kZd vkSlr Hkh vf/kd ik;k x;k gSA 15 fd-eh- izfr ?kaVk ls vf/kd okf"kZd vkSlr okyh iou xfr;ka dsoy xqtjkr vkSj rfeyukMq esa izsfkr dh xbZ gSaA jktLFkku] if’pe e/; izns’k] egkjk"Vª] mRrjh dukZVd rFkk lehiorhZ vka/kz izns’k ds dqN Hkkxksa vkSj if’peh ,oa iwohZ rVh; fdukjksa ds dqN Hkkxksa esa iou xfr 10 ls 15 fd-eh- izfr ?kaVk jghA mRrj Hkkjr esa okf"kZd vkSlr iou xfr 10 fd-eh- izfr ?kaVk ls vf/kd okys LVs’ku ux.; gSaA bl ’kks/k i= esa Hkkjr ds fofHkUu ks=ksa esa iouksa ds tyok;q foKku ,oa blds nh?kZ vof/k izo`fRr;ksa dk ewY;kadu fd;k x;k gS tgka iou ’kfDr dk ykHkizn rjhds ls mi;ksx fd;k tk ldrk gSA blds fy, izeq[k ks= xqtjkr ,oa lehiorhZ e/; izns’k] nfk.kh jktLFkku] mRrjh egkjk"Vª] mRrjh dukZVd] nfk.kh rfeyukMq] rVh; vka/kz izns’k rFkk if’peh rV ij xqtjkr ls xksok rd vkSj iwohZ rV ij dksydkrk ls ukxiV ue rd ds rVh; ks= gSaA This study analyses near-surface wind speed changes in India during 1961 to 2008. Consisting of monthly wind speed data of 171 stations, the results show that most of the stations in India have experienced significant weakening of wind speed, both at monthly and annual timescales. All-India averaged annual mean wind speed has decreased from 9.7 kmph in 1961 to 5.0 kmph in 2008 resulting in a 49% decrease. All India averaged rate of decrease in annual mean wind speed is -0.88 kmph/decade. On monthly scale, the largest rate of decline is in June (-1.33 kmph/decade) and the smallest is in October (-0.60 kmph/decade). Spatially, large declines are found in western India, south peninsula and the coastal areas while central, southeast and northeast India have the lesser change in wind speed. Significant weakening of wind speed has occurred primarily in regions along Gujarat, Maharashtra, Tamil Nadu, north Karnataka, coastal Orissa and coastal West Bengal which also have higher annual mean wind speed. Annual mean wind speeds exceeding 15 kmph are observed only over Gujarat and south Tamil Nadu. Some parts of Rajasthan, west Madhya Pradesh, Maharashtra, north Karnataka and adjoining Andhra Pradesh and some pockets along west and east coasts experience wind speeds of 10-15 kmph. Stations having annual mean wind speed exceeding 10 kmph are rare in north India. The study evaluates climatology of winds and its long-term trends over various regions of India where wind power can be profitably utilised. The prominent regions are in Gujarat and adjoining Madhya Pradesh, south Rajasthan, north Maharashtra, north Karnataka, south Tamil Nadu, coastal Andhra Pradesh and along the west coast from Gujarat to Goa and along the east coast from Kolkata to Nagapatinam. , number=3, journal=MAUSAM, year=2013, month=Jul., pages=417–436